Respuesta :

irjt

Answer:

( x + 5 ) · ( x + 1 )

Step-by-step explanation:

-Factoring by grouping-

First, split the middle term into two parts that are factorable by the other variables.

x² + x + 5x + 5

Factor the parts

x · ( x + 1 ) + 5 · ( x + 1 )

( x + 5 ) · ( x + 1 )

Answer:

C

Step-by-step explanation:

Given

x² + 6x + 5

Consider the factors of the constant term (+ 5) which sum to give the coefficient of the x- term (+ 6)

The factors are + 1 and + 5 , since

1 × 5 = + 5 and 1 + 5 = + 6, thus

x² +6x + 5 = (x + 1)(x + 5) → C

ACCESS MORE